Economic Landscape Sub Sektor Perikanan Pada Perekonomian Kabupaten Sidoarjo: Model Input Output Dan Analytical Hierarchy Process - Fauziyah Juanti; Aisah Jumiati; Edy Santoso (UPT Penerbitan Universitas Jember, 2014)
This research aimed to analyse the character of fisheries sub sector linkages with other sectors, output and income multiplier effects, the economic structure of fishery sub sector Sidoarjo,and the direction of fisheries sub sector development policy. The methods used Input Output (IO) model, Multiplier Product Matrix (MPM) and Analytical Hierarchy Process (AHP). Results of IO analysis indicated that the fisheries sub sector has greater backward linkages value than the value of the forward linkages. Thus, the fisheries sub sector has strong linkages value as the provider of input as output for other sectors of the economy with a multiplier value of output and higher incomes in other agricultural based sectors in the broad sense. Results of MPM analysis showed that a shift in some economic sectors particularly the fisheries sub-sector, from 8th position in 2006 to 7th position in 2011. AHP analysis showed that cultivation is the most effective activity alternative to improve the output and input of most economic sectors to harness natural resources owned by the Sidoarjo regency. The results of this study concluded that the fisheries sub sector has the potential to be cultivated as a sector that continues to have an important role for the economy of Sidoarjo.